2022
DOI: 10.3390/jof8070711
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Associated Pulmonary Mucormycosis

Abstract: COVID-19-associated mucormycosis (CAM) emerged as an epidemic in certain parts of the world amidst the global COVID-19 pandemic. While rhino–orbital mucormycosis was well reported during the pandemic, in the absence of routine diagnostic facilities including lower airway sampling, pulmonary mucormycosis was probably under-recognized. In this review, we have focused on the epidemiology and management of COVID-19-associated pulmonary mucormycosis (CAPM). CAPM is a deadly disease and mortality can be as high as 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Rhino-orbito-cerebral CAM should be described as associated with COVID-19 patients, but in this study, only pulmonary cases were detected, which represent less than 10% of CAM reported cases. Cases have been reported among immunocompromised hosts with worsening respiratory insufficiency, progressive pneumonia, persistent fever, and organ failure [50].…”
Section: Discussionmentioning
confidence: 99%
“…Rhino-orbito-cerebral CAM should be described as associated with COVID-19 patients, but in this study, only pulmonary cases were detected, which represent less than 10% of CAM reported cases. Cases have been reported among immunocompromised hosts with worsening respiratory insufficiency, progressive pneumonia, persistent fever, and organ failure [50].…”
Section: Discussionmentioning
confidence: 99%
“…Imagiologic findings are also unspecific and may include pulmonary infiltrates, parenchymal consolidation, multiple nodular lesions, pleural effusion, thick-walled cavities, mediastinal or hilar lymphadenopathy, and pneumothorax. The reverse halo sign is often associated with mucormycosis but was only described in up to 18% of cases [11,12]. Combined medical and surgical treatment is more effective than pharmacological treatment alone; however, in this case, only systemic antifungal therapy could be offered because the patient's clinical condition did…”
Section: Discussionmentioning
confidence: 85%
“…10 Somehow till date no reliable biomarkers and molecular test etc is available for mucormycosis. 11 Mucormycosis can easily be diagnosed clinically if the most common rhino-orbito-cerebral site is involved. The Time interval of diagnosis from Covid to mucormycosis was near 15 days; among them, only 10% were observed to have PMM.…”
Section: Discussionmentioning
confidence: 99%
“…10 It remained difficult to diagnose isolated PMM cases during active Covid pneumonia but somehow it was reported with high mortality of >80% in the absence of early clinical suspicion and treatment. 11 Most of these cases belonged to mechanical ventilator group, in association with diabetes, systemic high dose steroid, and other immunomodulator therapy like Tocilizumab, or with leucopenia and or lymphopenia. 7,9 In our case a history of covid treatment was present without the documentation of covid positivity.…”
Section: Discussionmentioning
confidence: 99%